1971
DOI: 10.1111/j.1540-4560.1971.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value Gap between Police and Policed1

Abstract: This article describes a study on the value patterns of a midwestern municipal police force, and compares police values with those of representative samples of black and white Americans. The data on police values support the hypotheses that personality factors and social backgrounds are more important than occupational socialization in understanding police value systems. The police values are not necessarily representative of American value patterns, either black or white, suggesting that either more different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 12 publications
4
68
1
Order By: Relevance
“…Rokeach, Miller, and Synder (1971) found that police officers, prior to entering the force, held similar values to those they displayed later in their careers. Crank and Caldero (1999) substantively expanded on this point of view in research demonstrating that police officer values changed little over time, including pre-and post-entry into the force.…”
Section: Implications For the Policing Literaturesupporting
confidence: 52%
“…Rokeach, Miller, and Synder (1971) found that police officers, prior to entering the force, held similar values to those they displayed later in their careers. Crank and Caldero (1999) substantively expanded on this point of view in research demonstrating that police officer values changed little over time, including pre-and post-entry into the force.…”
Section: Implications For the Policing Literaturesupporting
confidence: 52%
“…Second, the only empirical research they brought to bear on the measurement of the noble cause was Rokeach's value survey (Rokeach, Miller, & Snyder, 1971). This value survey has shown an alignment of the police on particular value clusters.…”
Section: The Noble Cause In Contemporary Researchmentioning
confidence: 99%
“…Characteristics that have been defined as common for police officers are attributes such as courage, authoritarianism, cynicism and aggression (Lefkowitz 1975, Twersky-Glasner 2005, as well as suspicion, conventionality and isolation (Evans et al 1992, Rokeach et al 1971, Skolnick 1994, Vastola 1978. Balch (1972) also highlights authoritarianism as an important element of police officers" personalities.…”
Section: Definition Of Police Personalitymentioning
confidence: 99%